The Effectiveness of Picture Series as a Media to Improve Students' Writing Skill - Wahyu Ilmillahdini, Yayi; Sumarsono, Puji (University of Muhammadiyah Malang, 2014)
The Effectiveness of Picture Series as a Media to Improve Students' Writing Skill